Türkiye'de İdari Reform Çalışmalarının Tarihsel Perspektif Açısından Değerlendirilmesi - Mamur Işıkçı, Yasemin (Muş Alparslan Üniversitesi, 2017)
Neoliberal policies, which were becoming more widespread with globalization, necessitated a change in the role of the state, and therefore the notion of interventionist state which was legitimated in the 1930’s was replaced by the regulatory state in the 1980’s. The aim of this study is to analyze the administrative reforms in the public administration area historically as regards the process of change in the role of the state.  The analysis was based on expert reports, development plans and implementation. Although it is directly related to the research, European Union Progress Reports were excluded from the scope of this study. After the administrative reforms in Turkey were separated historically, those made in the post-2000 era have been thoroughly examined, and an evaluation of the success and the future of these efforts has been provided. At the end of the study, it was determined that administrative reforms made in the Republican period in Turkey followed a narrow-scoped and isolated path that focused more on organizational issues until the 1980’s, whereas more inclusive and radical changes were implemented after the 1980’s.

Küreselleşme ile birlikte gittikçe yaygınlaşan neo-liberal politikalar devletin rolünde de bir değişimi zorunlu kılmış, 1930’lu yıllarda meşruiyet kazanmış olan müdahaleci devlet anlayışının yerini, 1980’li yıllardan sonra düzenleyici devlet anlayışı almıştır. Bu çalışmanın amacı; yönetimi alanındaki idari reformları devletin rolündeki değişim süreci ile birlikte tarihsel olarak analiz etmektir. Söz konusu analiz, uzman raporları, kalkınma planları, Avrupa Birliği İlerleme Raporları ve uygulama üzerinden yapılmıştır. Türkiye’de yapılan idari reform çalışmaları tarihsel olarak dönemlere ayrıldıktan sonra, 2000 yılı sonrası yeniden yapılanma çalışmaları ayrıca irdelenmiş ve son aşamada da bu çalışmaların başarısı ve geleceği hakkında bir değerlendirme yapılmıştır. Çalışma sonunda Türkiye’de cumhuriyet tarihinde yapılan idari düzenlemelerin 1980’li yıllara kadar dar kapsamlı ve daha çok örgütsel sorunları kapsayan kapalı bir anlayış hakimken, 1980’li yıllardan sonra daha kapsayıcı ve köklü değişimleri içerdiği belirlenmiştir.
Evaluation of Administrative Reforms with Regard to Historical Perspective in Turkey
anemon
Keywords: Administrative Reform; Public Administration; Globalization; Turkey; İdari Reform; Kamu Yönetimi; Küreselleşme; Türkiye